CHANGES IN MUSIC COURSES REQUIRED AT PRESENT TIME: IN THE CONTEXT OF SCHOOL EDUCATION SYSTEM: वर्तमान समयानुसार संगीत पाठ्यक्रमों में बदलाव की आवश्यकता: विद्यालयीन शिक्षण प्रणाली के सन्दर्भ में - Taylor, Sharmila; Gupta, Himani (International Journal of Research -GRANTHAALAYAH, 2015)
Education is a natural process of human life and education has an important place in human life. It is very important for a human being to get education to fulfill the needs of his life. But to get information about a subject only by reading any books can not be considered the full meaning of education, but to remember, contemplate, understand its meaning and use it successfully in life, education in the right way is. Literal meaning of education - "The Hindi word for education is derived from Sanskrit teaching, which means to learn or to learn. Another word from the same Sanskrit teaching of Sanskrit is also made, which means to teach. Education and teaching in its original sense may have similar meanings, as both words are formed from a single metal, but the term education is now used in the combined sense of both learning and teaching. ' शिक्षा मानव जीवन की एक स्वाभाविक प्रकिया है और मानव जीवन में शिक्षा का महत्त्वपूर्ण स्थान है। मानव को अपने जीवन की आवश्यकताओं की पूर्ति हेतुु शिक्षा प्राप्त करना अति आवश्यक है। परन्तु केवल किन्हीं पुस्तकों को पढ़कर किसी विषय की जानकारी प्राप्त कर लेने को ही शिक्षा का पूर्ण अर्थ नहीं माना जा सकता बल्कि उस प्राप्त जानकारी का स्मरण करना, मनन करना, उसका अर्थ समझना तथा उसका उपयोग सफलता पूर्वक जीवन में करना ही सही मायनों में शिक्षा है। शिक्षा का शाब्दिक अर्थ - ‘‘हिन्दी का शिक्षा शब्द संस्कृत की शिक्षा धातु से बना है, जिसका अर्थ है सीख अथवा सीखना। संस्कृत की इसी शिक्षा धातु से एक अन्य शब्द शिक्षण भी बना है, जिसका अर्थ है सिखाना। अपने मूल अर्थ में शिक्षा और शिक्षण के समान अर्थ हो सकते हैं, क्योंकि दोनों शब्द एक धातु से ही बने हैं, परन्तु शिक्षा शब्द अब सीखने और सिखाने दोनों के संयुक्त अर्थ में प्रयोग किया जाता है।‘